A Novel Zinc (II) Porphyrin Is Synergistic with PEV2 Bacteriophage against Pseudomonas aeruginosa Infections - Jessica Geyer; Kristen A. Krupa; Zachary M. Harris; Ying Sun; Lokesh Sharma; Silvia Würstle; Buqu Hu; Gail Stanley; Govindarajan Rajagopalan; Erin Pellot; Jonathan L. Koff; Jayne B. Robinson (MDPI AG, 2023)
Pseudomonas aeruginosa (PsA) is an opportunistic bacterial pathogen that causes life-threatening infections in individuals with compromised immune systems and exacerbates health concerns for those with cystic fibrosis (CF). PsA rapidly develops antibiotic resistance; thus, novel therapeutics are urgently needed to effectively combat this pathogen. Previously, we have shown that a novel cationic Zinc (II) porphyrin (ZnPor) has potent bactericidal activity against planktonic and biofilm-associated PsA cells, and disassembles the biofilm matrix via interactions with eDNA In the present study, we report that ZnPor caused a significant decrease in PsA populations in mouse lungs within an in vivo model of PsA pulmonary infection. Additionally, when combined with an obligately lytic phage PEV2, ZnPor at its minimum inhibitory concentration (MIC) displayed synergy against PsA in an established in vitro lung model resulting in greater protection of H441 lung cells versus either treatment alone. Concentrations above the minimum bactericidal concentration (MBC) of ZnPor were not toxic to H441 cells; however, no synergy was observed. This dose-dependent response is likely due to ZnPor's antiviral activity, reported herein. Together, these findings show the utility of ZnPor alone, and its synergy with PEV2, which could be a tunable combination used in the treatment of antibiotic-resistant infections.